2011
DOI: 10.1039/c1cc12857d
|View full text |Cite
|
Sign up to set email alerts
|

Methanol triggered ligand flip isomerization in a binuclear copper(i) complex and the luminescence response

Abstract: Methanol drives the blue emissive complex, [Cu(2)(dppy)(3)(MeCN)](BF(4))(2) (dppy = diphenylphosphino-pyridine), with a head-to-tail arrangement of the three bridging phosphine ligands to convert to its linkage isomer (head-to-head, green emissive) in the solid state, and the transformation could be reversibly realized through recrystallization in different solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…X-Ray single crystal structural analysis revealed that the two compounds are linkage isomers, 66 having a head-to-tail (HT) arrangement of the three bridging dppy ligands while 67 a head-to-head (HH) configuration (Scheme 3). [66]. The conversion from 66 to 67·MeOH could also be performed by exposure of solid 66 to MeOH vapor, and the process was fully reversed when the methanol adduct was recrystallized from MeCN/Et 2 O.…”
Section: Luminescence Vapochromismmentioning
confidence: 99%
See 1 more Smart Citation
“…X-Ray single crystal structural analysis revealed that the two compounds are linkage isomers, 66 having a head-to-tail (HT) arrangement of the three bridging dppy ligands while 67 a head-to-head (HH) configuration (Scheme 3). [66]. The conversion from 66 to 67·MeOH could also be performed by exposure of solid 66 to MeOH vapor, and the process was fully reversed when the methanol adduct was recrystallized from MeCN/Et 2 O.…”
Section: Luminescence Vapochromismmentioning
confidence: 99%
“…On the basis of the energy Stokes shifts and lifetimes, different contribution from 3 XMCT and 3 MC were suggested for the compounds" CC emissions. Wang et al reported a dinuclear copper(I) complex that undergoes methanol-responsive luminescence change through structural isomerization [66]. Compound [Cu 2 (dppy) 3 (MeCN)](BF 4 ) 2 (dppy = diphenylphosphino-pyridine), 66, was prepared by reaction of [Cu(MeCN) 4 ]BF 4 with dppy in 2 : 3 ratio in MeCN.…”
Section: Luminescence Vapochromismmentioning
confidence: 99%
“…18 Recently, Wang and co-workers reported that methanol drives the conversion of binuclear Cu I complex 8 from one linkage isomer to another in the solid state ( Figure 5), although the methanol does not coordinate directly to the metal center. 19 The head-to-tail isomer (8a) emits blue light in the solid state and can be transformed to the green-emitting head-to-head isomer (8b) by exposure to methanol vapor. Recrystallisation from MeCN/Et 2 O regenerates the headto-tail isomer.…”
Section: Chemically Responsive Solid State Materialsmentioning
confidence: 99%
“…For example, solvent molecules may participate in the excited states of the whole cluster through binding to metal ions. Free solvent molecules may also affect weak interactions such as metallophilic contacts, aromatic π–π stacking, and/or hydrogen bonds to influence the luminescence properties . Therefore, these complexes have potential applications in sensing of volatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%